Hyperborea w wybranych pismach nowożytnych uczonych francuskich - aspekt geograficzny w kontekście rosyjskim (Heteroglossia – studia kulturoznawczo-filologiczne, 2023)
This article analyzes the views of six French scholars in terms of the relationship between Hyperborea and Russia. They are in chronological order: M.-A. Baudrand (1682), S. Pelloutier (1740), N. Freret (1744/1753), J.S. Bailly (1779), P.H. Larcher (1802) and M.-N. Bouillet (1826). The theses of these researchers were largely dependent on F. Clüver (1616). These erudites were concerned not so much with Russia as a Hyperborean country, but with the geographic location of the Hyperborean ancestral homeland. Consequently, their analyzes had almost nothing to do with Russia. Only some areas of Russia (Nowa Zemlya, Western Siberia) and territories beyond its borders (Greenland, Spitsbergen) were indicated without emphasizing the connection between Russia and the „chosen people” of Greco-Roman antiquity. In this way, in the science of that time, data that was considered scientific at the time was clearly separated from ideological and propaganda data. The links between Hyperborea and Russia were pointed out only by P.H. Larcher (1802), following the opinion of J. Rennell (1800). This was in the first phase of the so-called Napoleonic Wars. Russia was already involved in the conflict with France. It can therefore be said that in these circumstances, linking Russia with Hyperborea, i.e. a kind of ennoblement of the Russian Empire, could have had a certain political subtext. On the English side, it was a kind of indication of the high position of the ally in the hierarchy of European powers. On the other hand, for P.H. Larcher as a Frenchman defeating the armies of Hyperborean Russia is a prestigious victory over an opponent covered with a halo of centuries-old glory. However, both for French scholars who wrote earlier and those who wrote after the fall of Napoleon, the link between Russia and Hyperborea was of little importance. They were engaged in science, not propaganda. These erudites only pointed to the fact that certain areas, which in their time or belonged to Russia, could have been inhabited in the distant past by peoples referred to as Hyperboreans. Russia, on the other hand, was for these scholars only synonymous with a country of tough people, hardened by the harsh climate. Such a Russia has also become a partner of European countries and one of the undisputed European powers. Deeper connections between Russia and Hyperborea were undoubtedly important to Russian patriots, becoming the basis of a romantic legend about the genesis of the tsarist state. The foundations for this legend were laid by Byzantine historiography, whose representative was Nicephorus Gregoras.